Simultaneous satellite and riometer measurements of particles during solar cosmic ray events. - Baker, M. B.; Satterblom, P. R.; Masley, A. J.; Goedeke, A. D. (1972)
The expected 30 and 50 MHz riometer absorptions have been calculated for three events in 1969 using data from the MDAC-W charged particle experiment on OGO 6. Several times during each event, the satellite passed over the MDAC-W Arctic and Antarctic Geophysical Observatories. The calculated total absorption (using 2 minute averages of the data) agrees well with the measured absorption for the overpasses. The alpha particle and electron contributions usually amount to less than a few percent of the proton absorption. During the large November 2, 1969 event, however, the electrons produced the major part of the absorption up to the peak and a significant contribution during virtually its entire duration. With the two frequencies for which simultaneous riometer data were taken, it is possible to detect the softening of the particle spectra during the events, and the relative hardness differences between events.